Characterization, Dynamics, and Mechanism of CXCR4 Antagonists on a Constitutively Active Mutant. Issue 5 (16th May 2019) - Rosenberg, Eric M.; Harrison, Reed E.S.; Tsou, Lun Kelvin; Drucker, Natalie; Humphries, Brock; Rajasekaran, Deepa; Luker, Kathryn E.; Wu, Chien-Huang; Song, Jen-Shin; Wang, Chuan-Jen; Murphy, James W.; Cheng, Yung-Chi; et al.
Summary: The G protein-coupled receptor (GPCR) CXCR4 is a co-receptor for HIV and is involved in cancers and autoimmune diseases. We characterized five purine or quinazoline core polyamine pharmacophores used for targeting CXCR4 dysregulation in diseases. All were neutral antagonists for wild-type CXCR4 and two were biased antagonists with effects on β-arrestin-2 only at high concentrations. These compounds displayed various activities for a constitutively active mutant (CAM). We use the IT1t-CXCR4 crystal structure and molecular dynamics (MD) simulations to develop two hypotheses for the activation of the N119 3.35 A CAM. The N119 3.35 A mutation facilitates increased coupling of TM helices III and VI. IT1t deactivates the CAM by disrupting the coupling between TM helices III and VI, mediated primarily by residue F87 2.53 . Mutants of F87 2.53 in N119 3.35 A CXCR4 precluded constitutive signaling and prevented inverse agonism. This work characterizes CXCR4 ligands and provides a mechanism for N119 3.35 A constitutive activation. Graphical Abstract: Highlights: Antagonists of wild-type CXCR4 exhibit differential effects on the N119 3.35 A mutant The mutant's constitutive activity stems from residues forming a hydrophobic triad Perturbation of the hydrophobic triad via mutation ablates constitutive activity Abstract : In this work, Rosenberg and co-authors characterize several potent small-molecule CXCR4 antagonists. The authors discuss two different possible mechanisms for why the N119 3.35 A CXCR4 mutant exhibits constitutive signaling, providing biochemical evidence supporting the role of a "hydrophobic triad" observed only in the mutant.